Supercritical carbon dioxide extraction of constituents of pithecellobin jiringan seed and their identification using time of flight gas spectrometry - Che Yunus, Mohd. Azizi (2006)
Supercritical carbon dioxide (sCO 2) is a fluid state of carbon dioxide where it is held at or above its critical temperature and critical pressure. Carbon dioxide usually behaves as a gas in air at standard temperature and pressure (STP), or as a solid called dry ice when frozen.